Precision measurements of the np scattering differential cross section in the intermediate energy region - P. Mermod (2018)
In fast neutron cancer therapy, ∼50% of the cell damage is caused by recoil protons from neutron-proton (np) scattering. In the intermediate energy region, there is a need for unambiguous np scattering data with good precision in both the shape of the angular distribution and the absolute normalisation. The normalisation techniques have been reviewed for np scattering measurements as well as recent experimental results, particularly the data obtained at The Svedberg Laboratory at 96 and 162 MeV. In addition, to what extent systematic uncertainties in the np differential cross section might affect the determination of proton recoil kerma coefficients is investigated. © The Author 2007. Published by Oxford University Press. All rights reserved.